Vitamin D as Radiosensitizer: A Review in Cell Line - Fahmi Radityamurti; Fauzan Herdian; Tiara Bunga Mayang Permata; Handoko Handoko; Henry Kodrat; Endang Nuryadi; Heri Wibowo; Soehartati A Gondhowiardjo (Journal of Pharmacy and Nutrition Sciences, 2020)
Introduction: Vitamin D has been shown to have anti-cancer properties such as antioxidants, anti-proliferative, and cell differentiation. The property of vitamin D as an anticancer agent triggers researchers to find out whether vitamin D is useful as a radiosensitizer. Multiple studies have been carried out on cell lines in various types of cancer, but the benefits of vitamin D as a radiosensitizer still controversial. This paperwork aims to investigate the utilization of Vitamin D3 (Calcitriol) as radiosensitizer in various cell line through literature review. Methods: A systematic search of available medical literature databases was performed on in-vitro studies with Vitamin D as a radiosensitizer in all types of cell lines. A total of 11 in-vitro studies were evaluated. Results: Nine studies in this review showed a significant effect of Vitamin D as a radiosensitizer agent by promoting cytotoxic autophagy, increasing apoptosis, inhibiting of cell survival and proliferation, promoting gene in ReIB inhibition, inducing senescene and necrosis. The two remaining studies showed no significant effect in the radiosensitizing mechanism of Vitamin D due to lack of evidence in-vitro settings. Conclusion: Vitamin D have anticancer property and can be used as a radiosensitizer by imploring various mechanism pathways in various cell lines. Further research especially in-vivo settings need to be evaluated.